Ex Libris Bogny Jakubowskiej K. Wróblewska. - Wróblewska, Krystyna (1904-1994) (s.n.], 1966)
Przedstawia kwiat róży, wokół liści napis: Ex Libris Bogny Jakubowskiej. Pod wyobrażeniem autograf aut. i data.